Enhancing Security for Resource-Constrained Smart Cities IoT Applications: Optimizing Cryptographic Techniques with Effective Field Multipliers - Atef Ibrahim; Fayez Gebali (Cryptography)
The broadening adoption of interconnected systems within smart city environments is fundamental for the progression of digitally driven economies, enabling the refinement of city administration, the enhancement of public service delivery, and the fostering of ecologically sustainable progress, thereby aligning with global sustainability benchmarks. However, the pervasive distribution of Internet of things (IoT) apparatuses introduces substantial security risks, attributable to the confidential nature of processed data and the heightened susceptibility to cybernetic intrusions targeting essential infrastructure. Commonly, these devices exhibit deficiencies stemming from restricted computational capabilities and the absence of uniform security standards. The resolution of these security challenges is paramount for the full realization of the advantages afforded by IoT without compromising system integrity. Cryptographic protocols represent the most viable solutions for the mitigation of these security vulnerabilities. However, the limitations inherent in IoT edge nodes complicate the deployment of robust cryptographic algorithms, which are fundamentally reliant on finite-field multiplication operations. Consequently, the streamlined execution of this operation is pivotal, as it will facilitate the effective deployment of encryption algorithms on these resource-limited devices. Therefore, the presented research concentrates on the formulation of a spatially and energetically efficient hardware implementation for the finite-field multiplication operation. The proposed arithmetic unit demonstrates significant improvements in hardware efficiency and energy consumption compared to state-of-the-art designs, while its systolic architecture provides inherent timing-attack resistance through deterministic operation. The regular structure not only enables these performance advantages but also facilitates future integration of error-detection and masking techniques for comprehensive side-channel protection. This combination of efficiency and security makes the multiplier particularly suitable for integration within encryption processors in resource-constrained IoT edge nodes, where it can enable secure data communication in smart city applications without compromising operational effectiveness or urban development goals.